Ancient Greek doctrine of the parts of speech and the place of a participle in it - Tananushka, Kir A. (Journal of the Belarusian State University. Philology, 2019)
The article is devoted to history of emergence and development of the parts of speech theory in Ancient Greece and to the place of a participle in it. It is stated that the modern classification of the parts of speech originates in the grammatical theories of ancient Greeks. It is noted that the doctrine of the parts of speech begins to take shape at the late Plato, who distinguished the noun and the verb, and at Aristotle, who has added to the first two the conjunction and the article. The contribution to the development of the theory of the parts of speech of the representatives of the Stoic school (Diogenes of Babylon, Chrysippus, Antipater of Tarsus) is analysed, who have continued Plato’s and Aristotle’s researches and distinguished six parts of speech: the common noun, the proper name, the verb, the conjunction, the article, the adverb. The progress of grammar as a science in the doctrine of Alexandrian scholars (Aristarchus of Samothrace, Dionysius the Thracian, Apollonius Dyscolus) is noted, who distinguished eight parts of speech: the noun, the verb, the participle, the article, the pronoun, the preposition, the adverb, the conjunction. The evolution of Greek grammars’ ideas of a participle as a part of speech is described. Modern researches on the authorship of the term ἡ μετοχή ‘participle’ are analysed; it is noted that the Alexandrian scientists named the participle a special part of speech, which has a verbal-noun nature. It is concluded that the views of ancient Greek grammarians, concerning the system of parts of speech and the place of a participle in it, became the foundation of European linguistics.
Keywords: Ancient Greece; parts of speech; participle; the Stoics; the Alexandrians; Plato; Aristotle; Diogenes of Babylon; Chrysippus; Antipater of Tarsus; Aristarchus of Samothrace; Dionysius the Thracian; Apollonius Dyscolus